A ratchet spring structure can harvest waves with variable frequencies. (March 2023) - Lv, Xuhan; Yang, Yaodong; Zhang, Dongcai; Wang, Ziliang; Li, Kailin; Rao, Weifeng
Abstract: In order to collect the energy from ocean waves, an important problem need to solve is the mismatch between the external excitation and the resonant frequency of a harvester. Here, we design a ratchet spring structure to capture waves from a wide range of frequencies (1–19.7 Hz) and then convert into a specific frequency: the resonant frequency of cantilevers. The resulted harvester can also effectively alleviate hazardous problems caused by sudden changes in wave frequency. Advanced design tools including artificial neural network algorithms were used to quickly optimize the parameters. With a good power output (19.44 mW), this energy harvester shows promising potential to power marine sensors. Graphical Abstract: ga1 Highlights: A novel ratchet-spring structure can adapt to variable frequencies. A generated power of 19.44 mW is obtained from ultra-low frequency waves. Use neural network algorithms for fast parameter optimization.